AUTOMATISASI PENENTUAN JALUR KONEKSI INTERNET PADA TIGA PROVIDER - Galih Dwi Wicaksono; Haruno Sajati; Dwi Nugraheny (Compiler, 2016)
Along with the times, the computer network has undergone many changes from time to time. Eventually, internet network is known. To test the reachability of a host on an IP address (internet protocol) network and to measure the round-trip time for messages sent from the host to the destination, computer needs to perform ping process. Ping operates by sending ICMP (Internet Control Message Protocol) echo request packets to the target host and waiting for an ICMP response. internet connection lane determination automation uses three providers done by comparing the smallest average value of the result of the ping. The test results are printed in the form of a statistical summary of the response packets received, including the minimum, maximum and average round-trip time. The signal strength is not directly proportional to the value of average, because the signal strength is affected by the report the data RSCP, throughput and quality of services covering CSSR (Call Setup Success Ratio), CCSR (Call Completion Success Ratio), DCR (Dropped Call Ratio) and BCR (Blocked Call Ratio) which can be used to optimize the network.